Differing over Originary Violence: Between Girard and Gans - Bartlett, Andrew (Anthropoetics, 2023)
René Girard’s critical remarks on the originary hypothesis of Eric Gans in Evolution and Conversion (trans. 2007) risk closing off rather than opening up conversations between disciples of Gans and those of Girard. Any sense of moral superiority produced by preoccupation with scapegoats depends on a misreading of Girard. It is possible to think of Gans’ss originary language event as a process of morphogenesis; as morphogenesis dependent on mimetic processes, the originary event of language origin in Gans resembles the scapegoat mechanism of Girard. Although mindless collective murder is not central to Gans’ss originary thinking, a keen awareness of mimetic violence pervades the theory. Girard and Gans should be studied together, not kept apart.